Bollywood : the films! the songs! the stars! - Dasgupta, Arpita; Ausaja, S. M. M.; Bachchan, Amitabh, 1942- (London : Dorling Kindersley limited, 2017)
I abhor the title of this book. The Indian Film Industry is what I shall always refer to as Cinema in India. We are an independent crative industry and not a derivative; any attempt to imply otherwise, shall not find favour with me...
The beginnning 1913-1950. -- The Golden Age 1951-1960. -- Enter the glamour 1961-1973. -- Angry young men 1973 1981. -- The reign of kitsch 1981-1990. -- Family Matters 1991 1999. -- The age of big money 2000 present.
Keywords: ACTORES Y ACTRICES DE CINE -- INDIA; INDUSTRIA CINEMATOGRAFICA -- INDIA; CINE -- PRODUCCION Y DIRECCION